Rheological properties of titanium niobium based feedstocks for metal injection moulding / Rozie Nani Ahmad...[et al.] - Ahmad, Rozie Nani; Muhamad, Norhamidi; Sulong, Abu Bakar; Wahi, Azizah; Mohd Salleh, Farrahshaida (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The rheological properties are very important in the metal injection moulding (MIM) process where it can give indication of flow ability of mold feedstock during injection moulding. In this study, the rheological properties of Titanium Niobium based feedstock with polyethylene (PE) and palm stearin (PS) as binder which have different powder loadings were analyzed using a Shimadzu Flow tester CFT-500D capillary rheometer. The binder composition consists of 40% palm stearin and 60% polyethylene based on weight fraction. The palm stearin is selected because of its low cost, low viscosity and high decomposition temperature. Rheology properties such as flow activation energy E, moldability index αSTV, and flow behavior index n were determined. Results indicate that the Ti-6Al-7Nb feedstocks have a pseudoplastic behavior and the value of index n is an average of 0.43. All the powder loadings can be injected and the green part density results are obtained.